Place value: place quality and its impact on health, social, economic and environmental outcomes - Carmona, Matthew (Journal of urban design, 2019)
This paper explores the link between the quality of the built environment and its value, in health, social, economic and environmental terms. This is theorized as 'place value' which, alongside 'place quality', is conceptualized as existing within a virtuous loop in which quality dictates value and value defines quality. To test this, a systematic review brought together wide-ranging international research evidence. The work confirmed a range of definitive associations between the quality of place and its place derived value. It also makes a clear link back from the evidence on place value to the sorts of qualities that enhance or detract from that value. These, in turn, define the constituent elements of place quality.